Expression of membrane HSP70 on tumor cells during cultivation in 3D cultures - V. V. Kostenko; A. A. Boyko; M. V. Grechikhina; O. V. Ovsyanikova; A. M. Sapozhnikov (Медицинская иммунология, 2024)
Heat shock proteins of the 70 kDa family (HSP70) are intracellular chaperones necessary for the cell to maintain protein homeostasis. In the cytosol, under normal conditions, these proteins promote the correct folding of proteins, preventing their aggregation, and are involved in protein transport and cell survival. Among the HSP70, there is a pool of stress-inducible proteins Hsp70, which significantly increases in response to a number of stress factors and facilitates cell recovery after stress. Tumor cells, unlike normal, are characterized by the ability to present Hsp70 on the surface of the cell membrane. Membrane-bound Hsp70 can be considered as a danger signal and enhance or inhibit immune responses. A three-dimensional model of cells in the spheroids in varying degrees simulates the structural organization of solid tumors. In cultures of multicellular spheroids (3D), hypoxia and nutrient gradients are formed within the spheroids, which can affect the translocation of Hsp70 to the cell membrane. The purpose of this work was a comparative analysis of Hsp70 expression on tumor cells of various origins when cultivated in a monolayer state (2D) and 3D cultures. Analysis was carried out on breast and pancreatic tumor cell lines, colon and prostate carcinomas, and lymphomas using flow cytometry and confocal microscopy methods. Cultivation in 3D cultures was performed using the antiadhesive PolyHEMA substrate. The results showed that not all carcinomas from our panel express Hsp70 in both 2D and 3D cultures. Some tumor lines have membrane Hsp70 only in 3D cultures. Hsp70 expression was detected on: BT20 breast cancer cells; colon carcinoma SW837; pancreas PANC1; and prostate PC-3. Analysis of Hsp70-positive carcinomas of various localizations in 2D and 3D models may be useful for the application of antibodies against Hsp70 as a vector for the delivery of anticancer drugs.